2013
DOI: 10.1080/02508281.2013.11081741
|View full text |Cite
|
Sign up to set email alerts
|

Puzzles in Understanding Chinese Tourist Behaviour: Towards a Triple-C Gaze

Abstract: Considerable efforts are underway to understand the behaviours of the growing number of outbound Chinese tourists. Existing research has shown that this market is complex, and an awareness of regional differences, change within China, and sensitivity to other world views are needed to guide studies in this area. For western researchers, several puzzles require conceptual clarification. These items of interest include what motivates Chinese tourists and are their motives different from those of western tourists… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(46 citation statements)
references
References 61 publications
1
44
0
1
Order By: Relevance
“…The research team and assistants comprised a mix of Chinese nationals and western researchers and there is an appreciation that some of the symbolism in the photographs reflects what has been described as the triple gaze of Chinese tourists (cf. Pearce et al, 2013). It is suggested that attempts to look at symbolic meanings would require substantial direct consultation with those who write blogs and post the photographs.…”
Section: Conclusion and Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The research team and assistants comprised a mix of Chinese nationals and western researchers and there is an appreciation that some of the symbolism in the photographs reflects what has been described as the triple gaze of Chinese tourists (cf. Pearce et al, 2013). It is suggested that attempts to look at symbolic meanings would require substantial direct consultation with those who write blogs and post the photographs.…”
Section: Conclusion and Discussionmentioning
confidence: 98%
“…Several key factors, notably easier visa applications, a growing confidence in travelling overseas driven in part by enhanced English speaking-skills, and the availability of much web-based information, support more independent travel by Chinese tourists (Pearce, Wu, & Osmond, 2013). The group tour is still popular, but independent travel is growing at an extraordinary speed.…”
Section: Research Respondents: Chinese Tourists-a Growing and Changinmentioning
confidence: 99%
“…Eleven years on and arguably there remain many gaps in this research field, even though the Chinese market is now recognized as the leading international outbound tourism market (CIW, 2017). Undoubtedly, research into this important market has increased over the past decade, investigating such aspects as the motivations of the Chinese tourist (Fu, Cai, & Lehto, 2017;Pearce, Wu, & Osmond, 2013;Xiang, 2013); their vacation satisfaction (Chan, Hsu, & Baum, 2015;Chen, Fu, & Lehto, 2016), and information-seeking behavior (Kambele, Li, & Zhou, 2015). However, many gaps remain; one of which being their impact upon the hosts of a destination and how this rapidly growing market is accommodated by host communities.…”
Section: Introductionmentioning
confidence: 99%
“…In other words, the majority of studies are concerned with the photographic practices of Western (principally international) tourists; conversely, more limited attention has been paid to those of non-Western tourists. In particular, although China is now the world's largest source of international tourists, and research has begun to identify the factors that determine the behaviours of Chinese tourists in general (for example, Arlt, 2006;Nyiri, 2009;Pearce, Wu & Osmond, 2013), few if any attempts have been made to date to explore how and why they engage in photography in particular during their international travels. This is not to say that photography as both an historical and contemporary cultural phenomenon in China has not benefitted from academic scrutiny (Roberts, 2013).…”
Section: Introductionmentioning
confidence: 99%